Trends And Research Directions In Graphic Design For Social Values And Cultural Identity: A Systematic Literature Review - Nagi, Ereso; Nathalea, Mariam (University of Science and Computer Technology, 2025)
The dynamic development of graphic design has increasingly intersected with social values and cultural identity, reflecting how visual communication can both shape and preserve collective meaning. Despite its growing relevance, research on this intersection often appears fragmented across disciplines, leaving a need for integrative insights. This study aims to systematically review existing literature to map key trends and highlight future research opportunities in graphic design for social values and cultural identity. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 protocol, with the PCC model (Population, Concept, Context) as the guiding framework for formulating the research question and structuring the search strategy. Publications were identified from Scopus, Web of Science, and other peer-reviewed databases, then filtered through predefined inclusion and exclusion criteria before undergoing qualitative thematic synthesis. The review identifies four dominant themes: the role of design in cultural preservation, visual strategies for social advocacy, the integration of digital media in identity representation, and participatory approaches involving communities. Findings also indicate a shift from traditional aesthetic perspectives toward interdisciplinary practices that combine design, technology, and social sciences. This synthesis underscores the importance of positioning graphic design not only as an artistic practice but also as a cultural and social agent. The study concludes by outlining a future research agenda that integrates critical theory, participatory design, and digital innovation to advance graphic design’s contribution to cultural identity and social transformation.